CODESRIA Bulletin Online, No. 10, September 2024 - Selection Report 2023–2024 CODESRIA Meaning-Making Research Initiatives (MRI) - Research Programme, (CODESRIA Bulletin, 2024)
Following the resumption of programme activities at the Council in the latter half of 2023, the Research Programme successfully launched the third edition of the Meaning-making Research Initiative (MRI) grants. The first edition was held in 2017, followed by a double edition for 2018– 2019. Both editions were concluded by 2022 and the final set of papers and books that were judged publishable have now been published. The last of these set of articles are contained in Africa Development, Volume 48, No. 3, 2023 at https://doi.org/10.57054/ad.v48i3. The Meaning-making Research Initiative (MRI), launched in July 2017, serves as the Council’s primary vehicle for advancing research in the social sciences and humanities. In November 2023, three categories of calls (General, Special Call for Female Scholars, Advanced Senior Scholars) were advertised in English, French and Portuguese. The calls were specifically designed to align with the objectives of CODESRIA’s 2023–2027 Strategic Plan. This report provides information on the selection process, in the process also highlighting important lessons that applicants might find beneficial. It is divided into five sections: Analysis of Applications; Selection Process; Selected Proposals; Selection of Resource Persons; and Evaluators’ Insights. 1. ANALYSIS OF APPLICATIONS Applications Received Out of the total 391 applications received, 267 were in the category of MRI General, with 153 being group projects and 114 individual applications. Furthermore, there were 116 applications for the Special Call for Female Scholars and 9 for the Advanced Senior Research Fellowship. Figure 1: Breakdown of applications received. The Special Call for Female Scholars led to a significant representation of women among the applicants. Of the applicants, 61% were women and 39% were men, as depicted in Figure 2. Figure 2: Gender representation of applicants. Out of the 267 proposals submitted for the MRI General, 71 were coordinated by women and 196 by men. For the Special Call for Female Scholars, all 116 proposals were coordinated by women. For the 9 Advanced Senior Research Fellowship proposals 2 were coordinated by women and 7 by men. Figure 3: Gender representation of coordinators. Figure 4 illustrates the breakdown of proposals by language. Out of a total of 391 proposals, 263 were in English, 93 in French and 35 in Portuguese. Figure 4: Breakdown of proposals by language. Regional Representation of Applicants As illustrated on the map below, the geographical distribution of candidates shows a significant concentration of scholars from the West African region, representing 34% of all applications. Southern Africa is in second position, followed by East Africa. Central Africa and North Africa occupy the fourth and fifth positions, respectively. In response to the historic underrepresentation of some countries in CODESRIA programming, the Research Programme launched a targeted campaign from November to December 2023, reaching out to 117 research administrators and scholars at universities and research centres across Africa. Administrators were requested to share the calls and announce them within their academic and local research communities. Despite these efforts, regional disparities remain, highlighting the ongoing need for more targeted programming to enhance the participation of researchers from underrepresented regions and countries. It is important to note that the underrepresentation of certain regions in CODESRIA activities is a longstanding and persistent issue. The Council has implemented various initiatives aimed at addressing this disparity, particularly focusing on scholars from conflict-affected countries and those with significant underinvestment in research and higher education. For instance, CODESRIA has launched special initiatives in the Great Lakes region, the Sudan zone, Portuguese-speaking countries, and through the Island Initiative. Although these efforts have yielded mixed results, CODESRIA has persisted in working to address the issue including a recent initiative to also establish a partnership with the Arab Council for the Social Sciences called the Afro-Arab Initiative to further this mission. Despite these endeavours, the challenge of underrepresentation persists, necessitating further targeted initiatives to effectively promote greater inclusion, ensure more comprehensive coverage of the continent, and ultimately contribute to richer and more relevant scholarship. Map 1: Geographical distribution of MRI 2023-2024 applicants. Cartography by Khady Diop, CODESRIA (2024). 2. SELECTION PROCESS The Research Programme received just over 400 proposals across the three categories. After an initial screening for completeness, adequacy and duplicate submissions, the total was reduced to 391 proposals, distributed as follows: MRI General: 265 applications MRI Female Scholars: 115 applications MRI Senior Advanced Research Fellowship: 9 applications. A notable aspect of the 2024 applications was that all submissions for the Special Call for Female Scholars were collaborative, multi-country projects. Additionally, the General MRI call featured a significant number of collaborative projects. The selection process was carried out in three phases. First, CODESRIA’s evaluators’ databases were thoroughly reviewed and updated to include persons with proficiency in English, French and Portuguese. The Research Programme paid careful attention to manuscript themes and areas of expertise as they related to gaps in reviewers’/evaluators’ profiles. The final cohort of evaluators retained for the task of reviewing applications were selected based on their academic rigour, professional experience and geographic and linguistic representation. It is important to emphasise that academic rigour was a standard consideration. Second, applications for the General and Special Female Scholar categories were distributed to 49 evaluators, while the Advanced Senior Fellowship proposals were reviewed by members of the CODESRIA Scientific Committee. Reviewers were responsible for evaluating various aspects of the projects, including their strengths and weaknesses, theoretical and methodological clarity, originality and innovation. This involved assessing whether the project had been previously published, its intellectual contribution, methodological creativity, relevance to the Strategic Plan’s thematic priorities and its potential to contribute new knowledge. To ensure consistency, reviewers received a detailed memo outlining the Council’s expectations. Each proposal underwent a double- blind peer-review process. Reviewers were also requested to provide not only written feedback on each proposal but also a general report summarising the collection of applications they reviewed. An abbreviated version is the consolidated report provided in the last section of this report. The report is expected to assist the Council in refining its overall strategy to better support African researchers. It is important to note that the evaluation process extended beyond the anticipated timeframe as a result of the lack of responsiveness of some evaluators and their failure to reply to repeated reminders, despite their initial commitment to providing timely feedback. Third, a committee comprising members from the Research Programme and the Training, Grants and Fellowships (TGF) programme was formed to evaluate the review reports and make the necessary arbitrations where review reports needed such moderation. The selection process took into account several key factors, including the quality of the proposals (based on scores and written feedback from peer reviewers), gender inclusion, regional and linguistic balance, thematic focus and diversity needed for a pan-African Council like CODESRIA. A notable observation was the large number of applications focused on higher education themes. Since the TGF Programme runs special projects related to higher education, it was deemed necessary to balance the number of accepted proposals in this area. As a result, higher education applications were placed in competition with each other, with only three ultimately being selected for this edition of MRI. The TGF currently has many other projects in the area, which range in focus, including Higher Education Governance, Curriculum Reform, Graduate Employability, Research Capacity in African Universities, Decolonisation and Africanisation of Higher Education, Higher Education and Economic Development, Internationalisation and Global Competitiveness, Digital Transformation and E-Learning, Higher Education Funding and Financing, and the Future of Higher Education in Africa, among other themes. Indeed, the Council has just concluded a major pilot project on academic freedom and will launch a multi-year programme of research, monitoring and publications on how academic freedom concerns intersect with dynamics in higher education. The team also noted a significant number of proposals centred on Indigenous Knowledge Systems (IKS). In light of upcoming calls for the Mastercard-funded IKS project, these proposals have been earmarked for further consideration. The Council will shortly communicate to the applicants informing them of this forthcoming initiative. The team spent considerable time reviewing evaluators’ feedback on proposals from the Advanced Senior Research Fellowship. It was noted that some peer reviewers provided only limited insights. Ultimately, because of the lack of outstanding proposals that met the expectations outlined in the call and the constraints of limited funding, the Secretariat decided not to award any Advanced Senior Research Fellowships this time around. 3. SELECTED PROPOSALS After thorough deliberations, the committee preselected what it deemed to be the strongest proposals based on the criteria discussed above. Additionally, a list of alternative proposals was prepared to be considered for support in case any of the initially selected proposals failed to take up the offer. MRI General Out of the 267 proposals received, 185 were written in English, 53 in French and 29 in Portuguese. The committee recommended 11 proposals among those written in English, 5 in French and 2 in Portuguese. Additionally, one of the proposals written in French combines 2 individual candidates and a separate group of 3 members, which the committee suggested grouping together because of the relative proximity of their topic of research. MRI Special Call For Female Scholars Out of the 116 submissions received, 72 were written in English, 38 in French and 6 in Portuguese. The committee shortlisted 14 proposals in this category: 6 in English, 7 in French and 1 in Portuguese. The limited number of English proposals chosen, despite the high volume of submissions, reflects the lower than expected quality of the proposals and the relatively large number of projects centred on higher education. MRI Senior Advanced Fellowship Out of the 9 proposals received, 7 were written in English by male scholars and 2 in French by female scholars. The committee shortlisted 4 proposals: 3 in English and 1 in French. MRI 2023-2024 list of winners From the shortlist, the following 13 projects were selected in the end, including 2 individual and 11 group projects. MRI General Table 1: Winning proposals, MRI General, MRI 2023–2024 MRI Special Call for Female Scholars Table 2: Winning proposals, MRI Special Call for Female Scholars, MRI 2023–2024 Proﬁle of Selected Applicants Researchers: A total of 48 researchers are involved in these projects. Gender of project leaders: Male: 2 Female: 11 Gender of all project participants: Male: 13 Female: 35 Geographical spread: The researchers are drawn from 16 countries with the following distribution: West Africa: 23 Southern Africa: 3 Central Africa: 13 East Africa: 8 4. SELECTION OF RESOURCE PERSONS FOR THE 2023–2024 MRI PROJECTS The list of resource persons was compiled from the evaluators’ list and then refined to ensure balanced representation. This process included considerations such as research specialisation, publication record, experience in methodology training, geographical and linguistic diversity and gender inclusion. The selected resource persons will oversee the projects through to completion and provide pastoral guidance to scholars in their respective groups. The MRI Methodology and Scholarly Workshop, scheduled for 16–20 September 2024, will offer an opportunity for the scholars to meet resource persons for the first time. 5. EVALUATORS’ INSIGHTS As explained above, 49 evaluators were engaged to assess the proposals. They analysed applications using a set of criteria that included theoretical robustness and clarity, methodological rigour, conceptual creativity, innovative thinking and mastery of relevant literature. Additionally, evaluators were required to provide a template with specific assessment of individual proposals and an overall report summarising their overall assessment over the quality and general orientation of applications. On average, evaluators reviewed 17 proposals each, allowing them to observe recurring patterns across a wide range of projects. Their reports mainly highlighted the strengths and weaknesses of the applications, offering valuable insights into the overall quality of submissions. While most proposals aligned with CODESRIA’s priority themes and cross-cutting issues, many exhibited significant limitations that, to a large extent, affected their possibility of being selected. These limitations varied, but were based on individual writing skills and research backgrounds. Most proposals addressed themes related to higher education, economics and developmental issues, while fewer focused on historical or anthropological questions. Proposals submitted for the General call primarily focused on economic and developmental issues, with fewer addressing politics and democratisation. Notably, a significant number of proposals on higher education topics were submitted, particularly by English-speaking scholars. Overall, some proposals had marked deficiencies in the quality of writing and showed significant limitations in articulating a research problem and constructing clear research objectives. Proposals submitted for the Special Call for Female Scholars predominantly focused on sociological topics, as well as migration, climate change, gender and reproductive health, disability, resource conservation and governance issues. In general, the reports indicated that while the proposals were on familiar and well-researched areas, many exhibited several additional weaknesses. These included a lack of relevance and alignment with thematic priorities, originality and depth. Social problems were often transformed into scientific problems without sufficient theoretical reflection, and there was inadequate engagement with existing literature. There was generally a lack of familiarity with the knowledge produced by CODESRIA. Theoretical and conceptual weaknesses were detected, such as difficulties in defining core concepts and formulating a problem statement, as well as theoretical discussions that did not operationalise concepts. Methodologically, many proposals demonstrated a lack of requisite knowledge of research methods for the social sciences and humanities and failed to present sound empirical methodologies to properly address the core questions. These limitations heavily impacted the overall structure of a significant number of proposals, along with writing deficiencies. According to the majority of evaluators, a prevalent issue in the proposals—regardless of language—was the difficulty in formulating a clear research question and defining the problem to be investigated. Additionally, there was a general limitation in constructing a coherent and clear proposal, where all parts—such as the general context of the theme, problem statement, objectives, hypothesis and study methodology—were effectively integrated and in conversation with one another. As one evaluator pointed out: A research gap is a question or a problem that has not been answered by any of the existing studies or research in a given field. A well-defined and structured research problem is the heart of the research project. Most of the proposals examined lacked this important component of research. Some presented a vague research problem, while others did not have one at all. Some were not convincing enough, which is why the proposals were considered weak (...). On the other hand, while fewer in number compared to the overall submissions, the accepted proposals were characterised as insightful and innovative, with sound methodologies and well- grounded theories that effectively addressed the research problems. Similar to the Special Call For Female Scholars, many accepted proposals adopted a gendered lens to investigate diverse societal issues. Evaluators noted that these proposals demonstrated methodological robustness through clearly articulated methods and processes. As stated by one evaluator: Applicants clearly articulated the various methods and processes to be adopted for their projects, demonstrating methodological robustness. Given the project’s focus on meaning-making research, the originality and innovativeness in the proposals are particularly encouraging. All the proposals were well-positioned within the existing literature, and some also had practical relevance. Regarding the General calls, another evaluator mentioned: The proposals were very insightful and largely comprehensive, demonstrating the commitment of Africa’s researchers to breaking theoretical and conceptual grounds. These proposals have the potential to address gaps in academic literature and in practice. Overall, feedback from the reviewers highlights a significant disparity between the high expectations regarding quality, innovativeness and originality of thought inherent in the MRI scheme and the considerable number of poorly constructed proposals. Although CODESRIA has consistently conducted a variety of methodological seminars across its Research and Training programmes, there is a pressing need to provide support for proposal writing for early- and mid- career scholars. This intervention should be seen as complementing the work that universities on the continent do at graduate level, but for CODESRIA the pivot will be in sharpening the skills for advanced research for the cohort of proposals identified. This further raises the need for clearer communication around the strategic objectives of the MRI scheme, namely to support the development of cutting-edge ideas and innovative research within Africa. Similarly, evaluators noted that weaknesses identified in projects submitted under the Special Call for Female Scholars mirrored those in the General category. In comparative terms, French- speaking and Portuguese-speaking countries show lower levels of readiness in research skills. Many evaluators pointed out disparities in research development among these countries, which was evident in the submitted applications. SuggesDons for Future MRI Calls A common suggestion from nearly all evaluators was to organise proposal-writing workshops for prospective applicants in various countries and regions. These workshops would provide researchers with the opportunity to improve their writing skills for their projects. The overall recommendations include: Organize pre-proposal methodology workshops: Focus on research methodologies, research design and proposal writing to improve the quality of submissions. Expand methodological training seminars to include a focus on integrating all parts of a research proposal, such as the context, problem statement, objectives, hypothesis and methodology. MRI is setting a high bar, but the pool of scholars it targets is not adequately prepared and/or available. Host virtual informational sessions: Provide orientation and guidance for potential MRI candidates on important aspects to consider when submitting MRI proposals. Work with borderline submissions: Support scholars to rework proposals that present original and fresh ideas but may be weak in presentation, to prepare them for future funding support. Encourage collaborative research: Highlight the importance of collaborative rather than individual projects, and devise ways to bring researchers together around innovative projects. Promote in-depth understanding of the MRI scheme: Ensure that projects are better aligned with the objectives outlined in the MRI and the CODESRIA Strategic Plan. Offer guidance on aligning proposals with CODESRIA’s thematic priorities and cross-cutting issues, ensuring relevance and impact. Increase awareness about MRI grants: Create greater awareness about the kinds of proposals that would qualify for MRI grants. Innovation and originality need to be emphasised and demonstrated, even for senior scholars. Require familiarity with CODESRIA’s corpus of knowledge: Make it a requirement for proposals to demonstrate familiarity with the existing body of knowledge produced by CODESRIA on the proposed research topic. The use of CODICE should accordingly be encouraged. Extend evaluation time: Address concerns from evaluators about the need for more time to conduct thorough evaluations in future calls. Collaborate with African universities: Despite CODESRIA’s long investment in methodological seminars, there is a need to reinvest in methodological training and writing seminars by partnering with African universities. Address disparities among academics: Pay special attention to the comparatively weak proposals from African academics and researchers, particularly from Lusophone and Francophone countries.